Legal Protection of HARA Platform Users on the Service of Electronic Data Interchange - Nikmah Mentari; Ninis Nugraheni; Muhammad Annas (Universitas Ahmad Dahlan, 2023)
Introduction to the Problem: The digital era of technology has cut the role of third parties and made it easier for services to be run peer-to-peer; where parties can connect directly at a business scale. Business relations is always accompanied by contracts. However, nowadays conventional contracts have undergone disruption with the existence of blockchain technology. A smart contract is a contract model that uses technology that can execute the contents of the contract automatically. The existence of this technological sophistication also has implications for the exchange of data, particularly personal data. Personal data can be easily accessed through the data exchange process, but it is feared that data misuse will occur. In order to prevent the Electronic Data Interchange of personal data using this technology, data must be protected.Purpose/Objective Study: This study aims to examine the legal protection of users of the HARA platform who use smart contracts in electronic data interchange services.Design/Methodology/Approach: This research is normative juridical research with statutory and conceptual approaches.Findings: In this case, the protection includes preventive and repressive protection. Preventively through legislation with the presence of laws on ITE and laws on Personal Data Protection as well as internal regulation of platform providers, while repressively lawsuits can be carried out through litigation and non-litigation channels.Paper Type: Research Article